IDDAH DAN IHDAD BAGI PEREMPUAN DALAM HUKUM ISLAM DAN HUKUM POSITIF (STUDI ANALISIS PERSPEKTIF GENDER) - Fina Maulani Wahdah; Ach. Faisol; Dzulfikar Rodafi (Jurnal Hikmatina, 2021)
This study described the understanding of the law of Iddah and Ihdad in the Qur'an and Hadith as well as Positive Law. The purpose of this study was to understand the provisions of Iddah and Ihdad in Islamic Law and Positive Law by using Gender Analysis. In this case the wife whose husband died must carry out Iddah and Ihdad, for one hundred and thirty days, in order to honor the departure of her husband, the wife must refrain from things that can cause slander. The researcher used a qualitative approach to the type of library researc. The results of this study indicated that the prohibition of women who are carrying out the Iddah and Ihdad periods is forbidden to marry another man, it is forbidden to leave the house except for urgent reasons, it is obligatory to do Ihdad for women who are doing Ihdad In Islamic law, the Iddah period for a wife is four months and ten days. While Iddah and Ihdad for men are mentioned in the Association of Legislations relating to the Compilation of Islamic Law (2011) in Chapter XIX article 170 paragraph (2) it is stated that "Husbands who are left behind by their wives, carry out a period of mourning according to propriety".